2021
DOI: 10.1016/j.trim.2021.101410
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D and acute rejection in human kidney transplantation: A systematic review and meta-analysis study

Abstract: Background: Vitamin D (VitD) de ciency is associated with several diseases such as multiple sclerosis, rheumatoid arthritis, respiratory infection, and so forth. In the eld of transplantation (kidney transplantation), some studies reported that patients with VitD de ciency are of increased risk of acute rejection, but other studies did not show such a risk. On the other hand, since VitD is a modulatory factor and can reduce the in ammatory response, understanding the exact role of it in transplantation may con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Since vitamin D regulates the immune system, alteration in its level affects the outcome of allografts, e.g., acute cellular rejection (ACR) and infection [ 39 ]. Similarly, several other studies reported that transplanted patients have a higher risk of infections [ 36 , 37 , 167 , 168 , 169 ] and rejections [ 38 , 170 ]. Thus, vitamin D supplementation and tight follow-up of its level is important in transplant recipient patients [ 39 ].…”
Section: Vitamin D and Sirt1 In Relation To Non-communicable Diseases...mentioning
confidence: 71%
See 1 more Smart Citation
“…Since vitamin D regulates the immune system, alteration in its level affects the outcome of allografts, e.g., acute cellular rejection (ACR) and infection [ 39 ]. Similarly, several other studies reported that transplanted patients have a higher risk of infections [ 36 , 37 , 167 , 168 , 169 ] and rejections [ 38 , 170 ]. Thus, vitamin D supplementation and tight follow-up of its level is important in transplant recipient patients [ 39 ].…”
Section: Vitamin D and Sirt1 In Relation To Non-communicable Diseases...mentioning
confidence: 71%
“…Many of these are associated with a reduced level of SIRT1 as well [ 34 , 35 ]. Vitamin D levels may influence the risk of infections in kidney and liver transplant recipients [ 36 , 37 ] and the risk of acute rejection [ 38 , 39 ] and of new-onset diabetes after kidney transplantation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies that investigated the role of vitamin D supplementation therapy were excluded from this meta-analysis. Another recent meta-analysis of 14 studies by Mirzakhani et al focused only on the role of vitamin D on acute rejection following KT and revealed an 82% higher chance of acute rejection in patients suffering from vitamin D deficiency [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D lack is related with a few illnesses like various sclerosis, rheumatoid joint pain, respiratory contamination, etc. In the Field of transplantation (kidney transplantation) [22]. Vitamin D inadequacy has been related with respiratory pain disorder, pneumonic fibrosis expanded degrees of IL-2, and cardiovascular antagonistic events [23].…”
Section: Children and Young People With Corpulencementioning
confidence: 99%